RESEARCHES OF SOILSES SECONDARY CONSOLIDATION - Kapustin, Vladimir Vladimirovich; Khaustov, Vladimir Vasilyevich; Kapustin, Vladimir Korneliyevich (Journal of Applied Engineering Science, 2017)
If clayey soils are present in soil bases, the settlement of ground can develop during the entire service life. For the possibility of predicting the age-old sediments at the stage of engineering surveys, laboratory tests of soils in the odometer are carried out. Such tests do not fully reflect the processes occurring in the foundations of foundations of limited dimensions. For a more reliable prediction of age-old sediments, laboratory experiments are proposed not in the odometer, but in a special die assembly. The results of a long experiment with a sample of the Callovian clay of an undisturbed structure and comparison with field observations are presented.
Keywords: Ground; Foundation; Base; Compressibility; Sediment; Creep